Media Representation of Gender and Non-Normative Sexual Diversity Groups - Berlian Fika Rachma Ukhty (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2024)
This study examines how the media represents gender and non-normative sexual diversity groups based on news coverage of the ASEAN Queer Advocacy Week (AAW). A qualitative approach was employed, utilizing the critical constructionist paradigm and Entman’s framing analysis as the data analysis technique. Analysis of 20 news articles from five Indonesian media outlets revealed the following findings: detik.com, tribunnews.com, and cnnindonesia. com were unsupportive of the existence of gender and non- normative sexual diversity groups, whereas kompas.com and kumparan.com maintained a neutral stance on this issue. Media outlets employed religious, normative, and market-oriented perspectives in representing these groups in their news products. Four forms of stigma toward these groups were identified in media coverage: (1) contradictory to religion and morals, (2) deviance, (3) incompatibility with Indonesian law and culture, and (4) association with disease. Furthermore, not all media adhered to the Indonesian Press Council’s Guidelines for Reporting on Diversity Issues in their reporting on gender and non-normative sexual diversity groups. The media played a significant role in shaping societal perspectives on these groups through news coverage that led to widespread actions.